2019
DOI: 10.1111/jnc.14821
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II mediates the axonal trafficking of tyrosine hydroxylase and dopamine β‐hydroxylase mRNAs and enhances norepinephrine synthesis in primary sympathetic neurons

Abstract: In the sympatho‐adrenal system, angiotensin II (Ang II) acts as a key neuromodulatory component. At sympathetic nerve terminals, Ang II influences sympathetic transmission by enhancing norepinephrine (NE) synthesis, facilitating NE release and inhibiting NE uptake. Previously, it was demonstrated that tyrosine hydroxylase (TH) mRNA is trafficked to the distal axons of primary superior cervical ganglia (SCG) neurons, directed by a cis‐acting regulatory element (i.e. zipcode) located in the 3'UTR of the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The infusion of angiotensin II in striatum provoke local dopamine release (Brown, Steward et al 1996). Angiotensin II has been shown to regulate the synthesis of the enzymes involved in catecholamine biosynthesis (Aschrafi, Berndt et al 2019). Moreover, ACE2 has been reported in the mitochondria isolated form cell cultures derived from dopaminergic neurons (Costa-Besada, Valenzuela et al 2018).…”
Section: Circuits For Reward Motivation and Movementmentioning
confidence: 99%
“…The infusion of angiotensin II in striatum provoke local dopamine release (Brown, Steward et al 1996). Angiotensin II has been shown to regulate the synthesis of the enzymes involved in catecholamine biosynthesis (Aschrafi, Berndt et al 2019). Moreover, ACE2 has been reported in the mitochondria isolated form cell cultures derived from dopaminergic neurons (Costa-Besada, Valenzuela et al 2018).…”
Section: Circuits For Reward Motivation and Movementmentioning
confidence: 99%
“…In the brain, Ang II-dopamine interaction was initially suggested by microdialysis studies, which observed that acute striatal perfusion of Ang II led to striatal dopamine release that was inhibited by AT1 antagonists ( Brown et al, 1996 ; Mendelsohn et al, 1993 ). More recently, Ang II was observed to regulate the axonal synthesis of norepinephrine and dopamine by modulating trafficking and expression of tyrosine hydroxylase and dopamine β-hydroxylase, two key enzymes for catecholamine biosynthesis ( Aschrafi et al, 2019 ). We have shown counterregulation between dopamine and angiotensin receptors in the nigrostriatal system ( Villar-Cheda et al, 2014 , 2010 ), and dimerization between AT1 and D2 receptors in striatal neurons ( Martinez-Pinilla et al, 2015 ).…”
Section: The Brain Ras Dopamine and Rasmentioning
confidence: 99%
“…For their replication and neuronal dissemination, neuroinvasive viruses must express proteins that control vesicular traffic ( Enquist, 2012 ). Angiotensin II increases and mediates neuronal vesicular trafficking ( Wang et al, 2001 ; Aschrafi et al, 2019 ), and since the receptor binding site of S-glycoproteins in SARS-CoV-2 is structurally similar to angiotensin II, the virus might be capable of increasing and modulating the neuronal vesicular trafficking system in the same manner (see Figure 1B ). Moreover, as coronaviruses modify and assembly inside of structures derived from endoplasmic reticulum, we further suggest that SARS-CoV-2 could also utilize continuous longitudinally spanning endoplasmic reticula, which were described in the myelinated axons, and which are likely a continuation of the somatic organelles ( Gonzalez and Couve, 2014 ).…”
Section: Exploitation Of Subcellular Membrane Compartments and Intracmentioning
confidence: 99%